The Bedside Mobility Assessment Tool (BMAT) embedded in the new Mobility Screening and Solutions Tool (MSST): addressing inaccuracies - Teresa Boynton (BMC, 2024)
Abstract The Melillo et al. article: Reliability and validity of the Veterans Administration Mobility Screening and Solutions Tool (MSST) (Melillo et al, BMC Health Serv Res 22:1323, 2022) introduces the MSST, a derivative flowchart tool in which the Banner Bedside Mobility Assessment Tool (BMAT) is embedded. The authors identify similar goals for the MSST as those for the BMAT, i.e. determine real-time mobility status and choose safe patient handling and mobility (SPHM) equipment to complete transfer and mobility tasks. Further Melillo et al. indicate that goals included "revising and enhancing" and addressing "gaps" in the BMAT, as well as creating instructions for the four BMAT levels (sit and shake, stretch and point, stand, step: march-in-place, advance step and return) that are clear, understandable and comfortable to use. The authors indicate that another goal of the VA MSST is it "enables any healthcare worker at any time to accurately measure and communicate patient mobility and transfer equipment needs." The present article addresses inaccuracies observed in the Melillo et al. article and confusing elements found in the VA MSST flowchart. The present article is based on the author's involvement in developing the BMAT starting in 2003 along with teams from Banner Health and Liko/Hill-Rom which incorporated use of the BMAT by unlicensed assistive personnel (UAP) as a recheck or verification of earlier testing. The 2020 BMAT 2.0 clarified confusing elements identified in BMAT 1.0, i.e. items that needed to be revised or enhanced. BMAT 2.0 covered use of SPHM when testing, when completing care tasks and when progressing patients. The BMAT is primarily a nurse-driven mobility assessment tool created to not be overly prescriptive. BMAT was validated and determined to be reliable based on years of clinical utility studies and research in various settings across the continuum of care. It continues to be supported by a large medical equipment manufacturer who maintains the copyright license. Although the VA MSST flowchart has the four BMAT assessment levels embedded within it, for reasons outlined in this article, it is not feasible to use the VA MSST flowchart alongside or in conjunction with the BMAT 2.0.